Estrogen shields women from COVID-19 complications by reducing ER stress. (October 2020) - Shabbir, Sana; Hafeez, Assad; Rafiq, Muhammad Arshad; Khan, Muhammad Jawad
Abstract: Estrogen hormone acts as a potential key player in providing immunity against certain viral infection. It is found to be associated in providing immunity against acute lungs inflammation and influenza virus by modulating cytokines storm and mediating adaptive immune alterations respectively. Women are less affected by SARS-CoV-2 infection because of the possible influence of estrogen hormone as compared to men. We hypothesized that SARS-CoV-2 causes stress in endoplasmic reticulum (ER) which in turn aggravates the infection, estrogen hormone might play key role in decreasing ER stress by activating estrogen mediated signaling pathways, results in unfolded protein response (UPR). Estrogen governs degradation of phosphotidylinositol 4, 5-bisphosphate (PIP2 ) into diacylglycerol (DAG) and inositol triphosphate (IP3 ) with the help of phospholipase C. IP3 start in-fluxing Ca +2 ions that helps in UPR activation. To support our hypothesis, we analyzed the data of 162, 392 COVID-19 patients to determine the relation of this disease with gender. We observed that 26% of women and 74% of men were affected by SARS-CoV-2. It indicated that women are less affected because of the possible influence of estrogen hormone in women.